移动通信系统的安全性能预测方法 (2021)
本发明公开了一种移动通信系统的安全性能预测方法，包括确定信源发射天线的接收信噪比的近似值的步骤，基于接收信噪比的近似值确定概率密度函数和累积分布函数的步骤，基于概率密度函数和累积分布函数推导安全中断概率的下界闭合表达式的步骤，以及采用神经网络对安全中断概率性能进行预测的步骤；本发明通过以上步骤针对安全中断概率和非零安全容量概率推导出精确的闭合表达式，进而基于神经网络对移动通信物理层安全性能进行了智能预测，与现有的极限学习机、局部加权线性回归、支持向量机等方法进行了比较，取得了更好的安全性能预测效果。 The invention discloses a safety performance prediction method of a mobile communication system. The method comprises the following steps: determining an approximate value of a receiving signal-to-noise ratio of an information source transmitting antenna; a step of determining a probability density function and a cumulative distribution function based on the approximate value of the received signal to noise ratio, a step of deriving a lower bound closed expression of the safety outage probability based on the probability density function and the cumulative distribution function, and a step ofpredicting safety outage probability performance by using a neural network; according to the method, an accurate closed expression is derived for the safety outage probabil